Dragon spear - George, Jessica Day, 1976- (Bloomsbury, 2009)
Creel's adventures continue when she, her brother, and her betrothed travel across the seas to visit their dragon friends and become involved in a battle against an alien group of dragons that has kidnapped Queen Velika, endangering her and her expected litter of hatchlings.